Ergonomic assessment in metal-based small industries in Bogor Regency, Indonesia, 2019 - Prima Andriani; Mila Tejamaya; Baiduri Widanarko; Amelia Anggarawati Putri (Elsevier, 2021)
Objective: Small and medium-sized enterprises (SMEs) play a major role in economic growth and employment, and they come with a greater risk of work-related illnesses for workers. Metal-based SMEs are recognised as the sector with the most demanding physical work activities and awkward postures, which are considered risk factors of musculoskeletal disorders (MSDs). This study analysed the risk factors of MSDs associated with different work postures during production. Methods: Body postures were examined using the Rapid Entire Body Assessment (REBA) method, and the data on musculoskeletal symptoms were collected using the Nordic Musculoskeletal Questionnaire (NMQ). Results: The results were calculated using the REBA method to determine the level of risk of various postures, namely, low risk (3.6%), medium risk (25.0%), high risk (60.7%), and very high risk (10.7%). The NMQ results indicated that most of the symptoms and discomfort were in the lower back (65%), wrist (45%), shoulder (35%), and ankle (35%) regions. Conclusions: The physical factors contributed more to the musculoskeletal symptoms in the body regions affected. The use of tools in lifting activities could decrease the level of risk.